Organizing Dalam Perspektif Manajemen Pendidikan Islam (Telaah Al-Qur’an Surah Ali-Imran [3] Ayat 103) - Burhanudin (Yayasan Al-Afif, 2025)
Organizing can be understood as the importance of uniting in ranks to achieve a common goal. With cohesiveness and cooperation within the organization, we can achieve success and success. In surah ali-Imran verse 103 teaches the values of leadership, discipline and unity in organizing. The purpose of organizing is to create a clear structure in an organization, divide tasks and responsibilities efficiently, and organize human resources so that they can achieve organizational goals well. With good organization, an organization can run regularly, effectively and efficiently in achieving its vision and mission. Researchers conducted literature research focused on studying the organizational management function in the Al-Quran, using the perspective of Al-Quran Interpretation Experts. Researchers collected data from various literary sources such as books and articles that discuss organization in the Al-Quran. Through content analysis, researchers reduce, organize, and explain data to gain a comprehensive understanding of organization in Islamic education. tafsir approach based on al-Misbah, al-Qurtubi, ath-Thabari, al-Azhar, ibn Kathir, al-Bayan ruh, al-Maraghi, al-Mubin, Jalalain and al-Qur'an wa I'rabuh wa Bayanuh, then associated with organizing from the perspective of Islamic education management. The results concluded that Islam teaches various aspects of life that cannot be separated from the rules of Allah SWT. as stated in the Al-Qur'an, Surah Ali-Imran [3] verse 103, which explains that organizing is seen as one of the important functions of educational management. The concept of organizing from an Al-Quran perspective is interpreted through certain verses such as Surah as-Shaff verse 4 and other verses.